Analisis Sektor Unggulan Aceh Bagian Timur - Nurlina Nurlina; Puti Andiny; Maulia Sari (Universitas Samudra, 2019)
This study aims to analyze the leading sectors in the economy in Eastern Aceh. The data analysis method used is Location Quotient (LQ) analysis and Shift Share analysis. Based on the calculation of LQ, it is known that the leading sector of East Aceh Regency is the mining sector and the LQ excavation from 2010-2016 with an average of 1,68 (LQ>1). This is because the availability of mineral content in East Aceh Regency increases the regional economy. The leading sector of Langsa City is health services and social activities with an average LQ since 2010-2016 of 2,10 (LQ>1). The leading sector of Aceh Tamiang Regency is the mining sector and excavation with an average LQ from 2010-2016 of 1,77 (LQ>1). Based on the shift share analysis, it is explained that the highest sector providing an increase in Aceh's GDRP was in the agriculture, forestry and fisheries sectors, and it was in the East Aceh District and Aceh Tamiang District, while Langsa City was not included. The sector that contributes to the increase in Aceh's GDRP, in Langsa City the sector that provides the highest increase in Aceh's GDRP is the sector of large and retail trade, car and motorcycle repair.